Effect of single doses of citalopram and reboxetine on urethral pressure: A randomized, double‐blind, placebo‐ and active‐controlled three‐period crossover study in healthy women. Issue 6 (30th June 2022) - Christoffersen, Thea; Kornholt, Jonatan; Riis, Troels; Sonne, Jesper; Sonne, David P.; Klarskov, Niels
Abstract: Aims: Urethral closure function is essential for urinary continence in women and decreased urethral pressure is associated with stress urinary incontinence (SUI). For decades, the effects of serotonergic drugs on central neural control of urethral closure have been investigated and discussed. Epidemiological studies suggest that the use of selective serotonin reuptake inhibitors (SSRIs), such as citalopram, is associated with SUI. However, the literature findings are conflicting. This study aimed to evaluate citalopram's effect on opening urethral pressure (OUP) in healthy women. Methods: We conducted a randomized, double‐blind, placebo‐ and active‐controlled crossover study in 24 healthy women. On three study days, which were separated by 8 days of washout, the subjects received single doses of either 40 mg citalopram (and placeboreboxetine ), 8 mg reboxetine (and placebocitalopram ), or two placebos. Study drugs were administered at a 1‐h interval due to a difference in estimated time to peak plasma concentration ( t max ). We measured OUP with urethral pressure reflectometry under both resting and squeezing conditions of the pelvic floor at estimated t max for both study drugs (one timepoint). Results: Compared to placebo, citalopram increased OUP by 6.6 cmH2 0 (95% confidence interval [CI] 0.04–13.1, p  = 0.048) in resting condition. In squeezing condition, OUP increased by 7.1 cmH2 0 (95% CI: 1.3–12.9, p  = 0.01). Reboxetine increased OUP by 30.0 cmH2 0 in resting condition compared to placebo (95% CI: 23.5–36.5, p  < 0.001), and 27.0 cmH2 0 (95% CI: 21.2–32.8, p  < 0.001) in squeezing condition. Conclusion: Citalopram increased OUP slightly compared to placebo suggesting that SSRI treatment does not induce or aggravate SUI.